Manajemen Kurikulum 2013 Pada Mata Pelajaran Sejarah Kebudayaan Islam MTs At-Taufiq Bogem Diwek Jombang - Moch. Sya'roni Hasan; Mutakim Mutakim (Al-Idaroh: Jurnal Studi Manajemen Pendidikan Islam, 2019)
The 2013 curriculum aims to improve and improve the quality of national education specifically in character education. This was done to answer the changing times dynamically. MTs At-Taufiq is an institution under the auspices of an independent Foundation both in terms of ideas, operations and finance not dependent on the Foundation. include: (1) All school staff do the 2013 curriculum planning formulation at the beginning of the new school year. (2) The school forms the 2013 curriculum team. (3) Prepares the curriculum through the MGMP of Islamic Cultural History Teachers outside MTs At-Taufiq Bogem Diwek Jombang. (4) The preparation of the lesson schedule is formulated in a meeting at the beginning of the new school year. While the implementation of the 2013 curriculum at MTs At-Taufiq Bogem Diwek Jombang on the subjects of Islamic cultural history can be described as follows: (1) apperception. (2) Exploration. (3) Consolidation of learning (4) Formation of Attitudes, Competencies, and Character. (5) Conducting an Assessment. Evaluation of the Development of 2013 Curriculum in Islamic Cultural History Subjects at MTs At-Taufiq Bogem Diwek Jombang is as follows: (1) Evaluation is carried out taking findings in Islamic cultural history teachers in the field (2) These findings are submitted at monthly evaluation meetings. The 2013 curriculum evaluation is based on the 2013 curriculum goals and the institution's vision and mission.